Uniqueness of Malaysia’s Halal Gastronomy in Promoting Muslim-Friendly Tourism Hub - Siti Syahirah Saffinee; Mohammad Aizat Jamaludin; Wan Nazri Che Mat Safiee (HH Publisher, 2024)
Non-Indexed Publication